Surface-confined single-layer covalent organic frameworks: design, synthesis and application. (6th March 2020) - Cui, Daling; Perepichka, Dmitrii F.; MacLeod, Jennifer M.; Rosei, Federico
Abstract : This review describes the state of the art of surface-confined single-layer covalent organic frameworks, focusing on reticular design, synthesis approaches, and exploring applications in host/guest chemistry. Abstract : Two-dimensional (2D) nanomaterials, such as graphene and single layer covalent organic frameworks (sCOFs) are being widely studied due to their unusual structure/property relationships. sCOFs typically feature atomic thickness, intrinsic nanoscale porosity and a crystalline lattice. Compared to other organic 2D materials, sCOFs exhibit major advantages including topological designation and constitutional tunability. This review describes the state of the art of surface-confined sCOFs, emphasizing reticular design, synthesis approaches, and key challenges related to improving quality and exploring applications.